Natural corrosion inhibitor for corrosion protection of metal artefact: an overview - Musa, Muktaruddin; Ani, Mohd Hanafi; Othman, Raihan (Trans Tech Publications, Switzerland, 2013)
The degradation of most of metals, with the exception of gold is a universal reaction. It is a constant and on-going problems, make it often difficult to eliminate completely causing either industrial or heritage conservation losing a lot of money. One way and most practical for corrosion protection are using green inhibitor. Therefore it is widely use either industry or heritage conservation. Unfortunately, the inhibitors used in conservation are frequently hazardous to conservator, either through inhaler or touch with skin. Responding to this, several researches has been conducted to look into environmental friendly inhibitors or green inhibitors. This paper will review current practice use of inhibitor in metal preservation before propose a new inhibitor which been used a long time ago in Malay traditional practice in Keris preservation.